A novel strategy for developing a tetravalent vaccine (dvac) against dengue utilizing conserved regions from all DENV proteins. (March 2022) - Nasar, Sitara; Nasar, Zara; Iftikhar, Saima
Abstract: Dengue fever is a global health issue which is infecting millions of people each year and number of reported infections are constantly increasing. Though the only commercialized vaccine i.e. dengvaxia has banned in several countries due to its potential health risk, overall vaccine holds promising potential against viruses. In this study, we have developed a novel formulation of multi-epitope peptide vaccine (dvac), which utilizes peptides from each dengue protein with >80% sequence conservancy within each serotype and their respective genotypes. Simultaneous utilization of all dengue proteins and their conservancy among dengue virus genome is targeted to evoke balanced immunity against dengue serotypes without eliciting antibody-dependent enhancement and antigenic sin like response, which are primarily responsible for severe dengue fever. Immunoinformatic approaches are used to identify the potential of dvac in inducing cytotoxic T-lymphocytes, helper T-lymphocytes, Interleukin-4, Interferon-gamma and B-cell immune responses without inducing allergic responses. Cross-reactivity of dvac with human cellular machinery is also taken into consideration to avoid any cross-reactive pathogenicity. Furthermore, interaction of dvac with immune receptors i.e. toll-like receptors (TLR3 and TLR4) using molecular docking studies revealed favorable interaction between synthetic peptide and immune receptors. Our findings suggest that designed multi-epitope peptide holds great potential to evoke balanced immunity against all dengue serotypes without eliciting any significant harmful side-effects. Highlights: Developed a novel formulation of multi-epitope peptide vaccine (dvac), by utilizing peptides from each dengue protein. Immunoinformatic approaches are used to identify the potential of dvac in inducing T-cell and B-cell immune responses. Molecular docking studies revealed favorable interaction between synthetic peptide and immune receptors.